Profile of Pulmonary Tuberculosis Patients in Dr. Soetomo General Academic Hospital - Muhammad Dany Ramadhan; Aryati Aryati; Laksmi Wulandari (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis, which mainly attacks the lungs but can also infect other body organs. Tuberculosis is a global health problem that causes the highest death after Human Immunodeficiency Virus (HIV). Indonesia ranks third highest in the world, with 420,994 cases in 2017. This study aims to determine the profile of pulmonary tuberculosis patients at Dr. Soetomo General Academic Hospital, Surabaya from January 1st to December 31st, 2019. The research was conducted using a descriptive method by collecting secondary data, through medical records of pulmonary tuberculosis patients at the Inpatient Unit of Dr. Soetomo General Academic Hospital during January 1st - December 31st, 2019. The data obtained were processed according to gender, age, education, occupation, comorbidities, clinical symptoms, history of TB treatment, sputum examination results, and GeneXpert. This study uses total sampling presented in the form of pictures. The results showed that most of the patients were male (61.92%), aged 45-54 years old (25.13%), high school education level (56.48%), and private employees (34.45%). The most common comorbidities were diabetes mellitus (35.07%), the most clinical symptoms found were shortness of breath (29.56%), the complete history of TB treatment was first-line OAT (42.22%), as many as (77.97%) sputum examinations showed no data. Many (7.77%) GeneXpert results showed resistance to rifampicin after six months of therapy.